THE ROLE OF WOMEN IN THE LINGUISTIC PERSPECTIVE OF THE QUR’AN: A STUDY OF DILALAH AND NAHWIYAH: PERAN WANITA DALAM PERSPEKTIF LINGUISTIK AL-QUR’AN: STUDI DILALAH DAN NAHWIYAH - Devi Surya Aljanah Devi; Fachrul Ghazi Ayu; Ayu Aulia Ayu; Syaripudin Basyar Syaripudin; Sultan Syahrir Sultan (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2024)
The Qur’an, as a comprehensive source of knowledge, serves as a fundamental reference for scholars in understanding linguistic laws. Its miraculous nature provides guidance (Al-Huda) applicable across eras, fostering the development of broad sciences. Among the diverse vocabularies in the Qur’an, words related to “woman” hold significant linguistic and contextual value. This study focuses on exploring the role of womwn in the linguistic perspective analyzing their nahwiyah (syntax) aspects, a vital branch of Arabic linguistics. The research employs a qualitative method with a literature review approach, emphasizing textual analysis of verses and contextual interpretations (dilalah). Data is drawn from relevant linguistic literature and analyzed to uncover deeper insights into these terms. The findings indicate that the Qur’an contains several vocabulary words meaning “woman” in various forms, such as إمرئة (imra’ah), الأم (al-umm), بنت(bint), and نساء (nisa’). Their meanings can vary depending on the sentence context and syntactic structure. The study aims to inspire further research into similar vocabularies and their implications within Islamic and societal frameworks.